Exploring the impact of economic hardship on the development of self-esteem - Harris, Joshua William (Kansas State University, 2024)
This study examines the impact of economic hardship on self-esteem development using the family stress model (Conger et al., 1990) as a theoretical framework. Self-esteem serves as an indicator of current well-being and future success for both researchers and practitioners. This study focuses on understanding economic hardship's impact on self-esteem development through family dynamics and processes conceptualized by the family stress model. Using the National Longitudinal Study of Adolescent to Adult Health (ADD Health), a sample of 730 respondents is examined through structural equation modeling to assess economic hardship's impact on self-esteem development. The results indicate that while economic hardship has no significant effect on self-esteem development in this sample, the role of mothers has a significant and long-term impact on self-esteem in emerging adulthood. Moreover, when considering the effects that gender has on self-esteem development via moderation, neither male nor female emerging adults experienced differing effects between disrupted parenting and self-esteem. While researchers should continue to explore more research to understand the impact of economic hardship on self-esteem, the parent-to-adolescent relationship significantly impacts self-esteem development. Financial planners, counselors, and therapists are focused on wealth accumulation, maximization, and enjoyment for their clients. Their understanding of childhood experiences of economic hardship on self-esteem via family dynamics and processes helps them understand early indicators of academic and job performance, wealth accumulation, financial risk-taking, and seeking financial advice. To support their clients and the next generation, financial professionals' focus can remain and expand on family dynamics and processes that have affected and continue to affect financial wellness and decision-making and focus less on the economic background and previous economic hardship experienced by their family.
Keywords: Self-esteem; Family stress model